Stosowanie używek a czynniki społeczno-demograficzne = Applying of stimulants and social - demographic factors - Dorota Weber; Dorota Nalepa; Renata Rogala; Marianna Charzyńska-Gula (Kazimierz Wielki University, 2016)
Weber Dorota, Nalepa Dorota, Rogala Renata, Charzyńska-Gula Marianna. Stosowanie używek a czynniki społeczno-demograficzne = Applying of stimulants and social - demographic factors. Journal of Education, Health and Sport. 2016;6(6):135-145. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.54717 http://ojs.ukw.edu.pl/index.php/johs/article/view/3560   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016.   Stosowanie używek a czynniki społeczno-demograficzne Applying of stimulants and social-demographic factors   Dorota Weber1, Dorota Nalepa2, Renata Rogala3, Marianna Charzyńska-Gula4   1Absolwentka Kierunku Pielęgniarstwo -Warszawski Uniwersytet Medyczny 2Doktorantka Katedry Nefrologii Uniwersytetu Medycznego w Lublinie, adres email: nalepad1@wp.pl 3Doktorantka studiów doktoranckich w Zakładzie Kwalifikowanej Pomocy Medycznej z Pracownią Ratownictwa Medycznego Uniwersytetu Medycznego w Lublinie 4Państwowa Wyższa Szkoła Zawodowa im. prof. Stanisława Tarnowskiego w Tarnobrzegu       Streszczenie Wstęp. Autorzy wielu prac potwierdzają popularny pogląd, że "palacze piją, a pijący palą". Ponadto ci, którzy piją najwięcej, zwykle też najwięcej palą. Jednoczesne używanie tych dwóch środków stanowi istotne zagrożenie dla zdrowia publicznego. Badania przeprowadzane wśród osób leczonych z powodu alkoholizmu i innych uzależnień wykazały, że w okresie 12 lat zmarły 222 osoby spośród 845 badanych. Celem pracy jest ukazanie, czy czynniki społeczno - demograficzne mają wpływ na stosowanie używek takich jak:  papierosy i alkohol. Materiał i metody. Badania przeprowadzono w  2015 roku w jednej z lubelskiej przychodni. Do badań zakwalifikowano 148 respondentów. Zastosowaną metodą w badaniach był sondaż diagnostyczny a wykorzystaną techniką kwestionariusz wywiadu przeprowadzony wśród respondentów, w którym wykorzystano metryczkę i wywiad . Badaniem objęto 148 respondentów, których podzielono na 2 grupy: uczących się i pracujących. Wyniki. Badania własne ukazały, że palenie tytoniu to nałóg nie spotykany u 74,6% respondentów uczących się  i 46% pracujących. Osoby uczące się tj. w młodszym wieku, mniej palą niż osoby starsze. Analiza statystyczna wykazała, że alkoholu  nie pija tylko 9 badanych (13,8%) wśród  osób uczących się  i 21 (26,3%)wśród pracujących. Wnioski Według przedstawionych badań na stosowanie alkoholu wpływa zarówno wiek, płeć jak i miejsce zamieszkania, natomiast  na palenie papierosów ma wpływ wiek respondentów.   Słowa kluczowe: stosowanie używek, czynniki społeczno-demograficzne.   Abstract Introduction. A number of scientists confirm the common belief that "smokers drink and drunks smoke". In addition, those who abuse alcohol the most usually smoke excessively. Simultaneous abusing both of these substances poses a threat to public health. The research conducted among patients treated with the addiction to alcohol and other addictions as well has shown that in the span of twelve years, out of 845 examined patients, 222 persons died. The aim of this paper is to show whether  socio-demographic factors exert an impact on using such stimulants as: cigarettes and alcohol. Materials and methods. The research was carried out  in a clinic in Lublin in the year 2015. 148 respondents were qualified for the investigation. The method applied for the study was a diagnostic survey, and the technique used was a questionnaire conducted in the form of an interview with respondents, taking into account their birth certificate and an interview.  The investigation covered 148 persons,  who were split into 2 groups: the learning and the working ones. Findings. The investigation indicated that smoking nicotine is a habit which is not found in 74.6% studying persons and in 46% working persons.  Students, i.e. persons at a younger age, smoke less than older persons. The statistical analysis revealed that alcohol is not consumed by only 9 examined  persons (13.8%) out of the studying ones, and 21 (26.3%) out of the working ones. Conclusions. In the light of the research, alcohol consumption is linked with both age, gender and the place of living, whereas smoking cigarettes is connected with the age of the respondents.   Key words: use of stimulants, socio-demographic factors.